MANAGEMENT OF ENDOCRINE DISEASE: Reversible hypogonadotropic hypogonadism. Issue 6 (June 2016) - Dwyer, Andrew A; Raivio, Taneli; Pitteloud, Nelly
Abstract : Congenital hypogonadotropic hypogonadism (CHH) is characterized by lack of puberty and infertility. Traditionally, it has been considered a life-long condition yet cases of reversibility have been described wherein patients spontaneously recover function of the reproductive axis following treatment. Reversibility occurs in both male and female CHH cases and appears to be more common (~10–15%) than previously thought. These reversal patients span a range of GnRH deficiency from mild to severe and many reversal patients harbor mutations in genes underlying CHH. However, to date there are no clear factors for predicting reversible CHH. Importantly, recovery of reproductive axis function may not be permanent. Thus, CHH is not always life-long and the incidence of reversal warrants periodic treatment withdrawal with close monitoring and follow-up. Reversible CHH highlights the importance of environmental (epigenetic) factors such as sex steroid treatment on the reproductive axis in modifying the phenotype. This review provides an overview and an update on what is known about this phenomenon.